Regularity results for Kolmogorov equations in L²(H, μ) spaces and applications - Da Prato, G. (Український математичний журнал, 1997)
We consider the transition semigroup Rt =e tsA associated to an Ornstein—Uhlenbeck process in a Hilbert space H. We characterize, under suitable assumptions, the domain of A as a subspace W²,²(H, μ), where μ is the invariant measure associated to Rt . This characterization is then used to treat some Kolmogorov equations with variable coefficients. Розглядається перехідна пінгрупа Rt=etsA, що пов'язана з процесом Орнштейна-Уленбека у гілібертовому просторі H. При належних умонах находиться характеризація області визначення A як підпростору W²,²(H,μ), де μ— інваріантна міра, що асоціюється з Rt характеризація никористовується для розгляду деяких рівнянь Колмогорова зі змінними коефіцієнтами.